Supplier diversity journey: an empirical investigation - Priscila Laczynski de Souza Miguel; Andrea Lago da Silva (RAUSP Management Journal)
Purpose – This paper aims to investigate how purchasing organizations implement supplier diversity (SD) initiatives over time. Design/methodology/approach – A multiple case study approach was conducted. Data were collected through in-depth interviews with participants from purchasing organizations, intermediary organizations and diverse suppliers. Findings – The research suggests that the SD journey encompasses three different, but interrelated stages before full implementation is achieved: structuring, operation and adaptation. The findings also provide evidence that SD implementation in Brazil is highly influenced by the lack of a consistent knowledge base and the lack of legitimized intermediary organizations. Research limitations/implications – Using a temporal approach to understand how different practices suggested by the literature have been managed by practitioners over time, this study contributes to the understanding of the path to effective SD implementation and how intra- and interorganizational context influences this journey. Practical implications – By identifying which practices should be adopted during different phases of SD implementation and proposing ways to overcome some of the inherent challenges, managers can better plan and allocate resources for the adoption of a successful SD initiative. Social implications – This research demonstrates how organizations can promote diversity and reduce social and economic inequalities by buying from diverse suppliers. Originality/value – Using a temporal approach, the research empirically investigates how different purchasing organizations have implemented and managed the known practices and dealt with the challenges faced when trying to adopt SD.